Respon Pertumbuhan dan Hasil Garut (Maranta Arundinacea) Terhadap Pembumbunan dan Pemupukan Kalium - Rahmawati Fitria; Supriyono Supriyono; Sudadi Sudadi (Agrotechnology Research Journal, 2017)
This research aims to determine the arrowroot responses on piling and potassium fertilizer application on its growth and yield. This research was conducted in Experiment Field of Agriculture Faculty SebelasMaret University at Sukosari, Jumantono, Karanganyar using Randomized Completed Block Design (RCBD) factorial with two factors of piling and potassium fertilization.There are 2 levels of piling, consists of without piling treatment (P0) and with in piling (P1).There are 3 levels of potassium fertilization consist of  250 kg ha-1 KCl, 300 kg ha-1 KCl, and 350 kg ha-1 KCl. Observation variable consist of plant height, leaf number, tiller number, biomass fresh weight per plant, biomass dry weight per plant, tuber numbers per plant, tuber weights per plant, tuber weights per plot, tuber diameter, and tuber length. Data were analyzed using analysis of variance and if there is significant difference, continue with DMRT (Duncan’s Multiple Range Test) of 5% level. The result showed that treatment with in piling (P1) can tends to increase yield of arrowroot plant on tuber numbers per plant, tuber weights per plant, and tuber weights per plot. Potassium fertilizer treatment with  350 kg ha-1 dose KCl tends to increase at growth and yield in all variables except the tiller numbers.